Impacto social de la actividad crediticia del banco de la nación – Trujillo años 2006 - 2008 - Sabana Ramírez, María Isabel (2010)
The present is aimed at measuring the social impact of the credit of the National Bank in Trujillo, notably caused by the growth of the national banking system activity in which financial resources are needed so that people can in some way troubleshoot growing poverty, meet their basic needs and develop productive strategies through: grants, loans, or savings. According to the object of study identified elements of social impact and personal loans offered by the Bank of the Nation in the field of action of the Trujillo headquarters. Then proceeded to locate sources of information, making a compilation and review of the information obtained in order to demonstrate the social impact of the credit activity of the National Bank - see Trujillo. All this was subjected to critical analysis, which allowed to formulate conclusions and recommendations relating to present research findings. We are seeing there are improvements in the level of quality of life of the public sector, from access to the personal loan - public sector providers. As the performance improvements in the conditions of housing, access to training and skills, education and food improvement from changes in the family diet.